Immunogenicity of virus-like particles containing modified human immunodeficiency virus envelope proteins - Quan, Fu-Shi (2007)
Extensive glycosylation and variable loops of the HIV envelope protein (Env) are reported to shield some neutralizing epitopes. Here, we investigated the immunogenicity of mutated HIV Envs presented in virus-like particles (VLPs). We immunized mice with simian human immunodeficiency virus (SHIV) VLPs containing mutant HIV Env with reduced glycosylation (3G), variable loop-deleted mutations (dV1V2), or combinations of both types of mutations (3G-dV2−1G), and evaluated immune responses. Immune sera from mice that received VLPs with modified HIV Envs (3G or dV1V2) showed higher neutralizing activities against the homologous HIV 89.6 virus as well as heterologous viruses when compared with wild type SHIV VLP-immunized mice. Lymphocytes from immunized mice produced HIV Env-specific cytokines, with the 3G-dV2−1G mutant producing high levels of cytokines. Interestingly, both dendritic cells and B cells were found to interact with VLPs suggesting that VLPs are effective immunogens. Therefore, this study suggests that VLPs containing modified HIV Env have the potential to be developed as candidate vaccines capable of inducing cellular and humoral immune responses including neutralizing activities.